MAGNETIC COERCIVITY UNMIXING IN LOESS PALEOSOL SEQUENCE IN CHINESE LOESS PLATEAU THROUGH MAX UNMIX PROGRAM - Ainunnisa, Firadila
The largest loess area is located in north-central China, known as the Chinese Loess Plateau. This Chinese loess stratigraphy consists of loess and paleosols alternating layers. Various representations have been extracted from this loess-paleosol sequence, and have been used to reconstruct paleoclimatic changes, one of which is by using magnetic susceptibility. This research objective is to determine the magnetic coercivity contained in Chinese Loess Plateau samples, and to identify the magnetic minerals composition contained in the Chinese Loess Plateau samples. The result from the digitization process of the Isothermal Remanent Magnetization (IRM) curve of the magnetic field in Chinese Loess Plateau samples will be used as data. Unmixing method will be used, assisted by the MAX UnMix program to obtain the coercivity value of the magnetic mineral samples. The results from unmixing three types of samples, two dominant magnetic minerals were found in the sample. The results of unmixing the coercivity curves of each sample indicate the presence of high coercive magnetic mineralogy, which is more than 40 mT. Each sample has a coercivity value, ranging from 1.778 mT – 70.938 mT. The coercivity values differences in those three samples could be caused by magnetic mineral types and magnetic components quantity differences in each sample. These differences also 1ccurred due to the formation climate of each soil layer created from different climatic conditions at the time of its formation.